'As a Stranger Give it Welcome': Foreignness and Wonder in Jacobean London. Issue 2 (1st June 2022) - Potter, Lois
Abstract: The two early modern meanings of the word 'stranger' (someone one does not know; a foreigner) have become separated in modern English. This article looks at attitudes to the 'stranger' both as pathetic victim and as someone outside Anglophone language and culture, with special reference to the arrival of a Scottish king and his followers in 1603–04. Horatio's 'wondrous strange' (here, referring to the apparent ubiquity of the Ghost's voice) is as metatheatrical as Hamlet's later jokey comment on 'this fellow in the cellarage'. The language of 'wonder', a particularly Jacobean phenomenon, suggests that intense artistic experiences, like experiences of shock and horror, can make the spectator or listener – as Milton put it – 'marble with too much conceiving'.